2018
DOI: 10.1063/1.5040734
|View full text |Cite
|
Sign up to set email alerts
|

Dual-band electromagnetically induced transparency effect in a concentrically coupled asymmetric terahertz metamaterial

Abstract: We propose a scheme to achieve a dual-band electromagnetically induced transparency (EIT) effect in a planar terahertz metamaterial (MM), comprising an inner circular split ring resonator (CSRR) concentrically coupled to an outer asymmetric two-gap circular split ring resonator (ASRR). The scheme is numerically and theoretically analyzed. The dual-band EIT effect occurs as a result of the near field coupling between the resonant modes of the resonators comprising the MM configuration. It is observed that the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Papasimakis et al reported a similar phenomenon in the microwave domain using bilayered fish-scale metamaterials [79]. Later Tassin et al demonstrated EIT-like effects at the operational frequency range of 35-40 THz, which together with a set of other studies [80][81][82][83][84][85][86], formed the basis of metamaterial-based EIT/PIT research.…”
Section: Electromagnetically Induced Transparency (Eit) Effects In Terahertz Metamaterials Resonancesmentioning
confidence: 89%
“…Papasimakis et al reported a similar phenomenon in the microwave domain using bilayered fish-scale metamaterials [79]. Later Tassin et al demonstrated EIT-like effects at the operational frequency range of 35-40 THz, which together with a set of other studies [80][81][82][83][84][85][86], formed the basis of metamaterial-based EIT/PIT research.…”
Section: Electromagnetically Induced Transparency (Eit) Effects In Terahertz Metamaterials Resonancesmentioning
confidence: 89%
“…More recent attention has focused on the multi-band PIT effect in THz metamaterials, with multiple transparent windows induced by the coupling effect between THz resonators [37][38][39] . With regard to the switching of the multi-band PIT effect, the quasi-dark resonator is introduced to weakly couple with the free space electromagnetic fields [40,41] . Thus, the multi-band PIT effect occurs, stemming from the near-field electrical coupling between the resonant modes in a three-level system comprising the bright mode, dark mode, and quasi-dark mode [42] .…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the above limitation, a variety of THz MSs with multi-band EIT windows were designed to actively modulate resonance properties by means of different approaches, including mechanical movement, phase change material, and graphene. For example, Devi et al designed a concentrically coupled asymmetric THz MS to obtain a dual-band EIT effect; moreover, the dual-band EIT effect can be effectively modulated by rotating the element angle or by changing the asymmetric degree of the unit cell [ 11 ]. Chen et al demonstrated an actively tunable dual-band EIT window in a VO 2 -integrated MSs [ 12 ].…”
Section: Introductionmentioning
confidence: 99%